PENINGKATAN AKTIFITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN KESEHATAN, KESELAMATAN KERJA (K3) DAN HIGIENE SANITASI DENGAN MENGGUNAKAN MEDIA POWER POINT DI SMK NEGERI 3 KOTA SOLOK - Sarah, Sarah; Baidar, Baidar; Elida, Elida (Journal of Home Economics and Tourism, 2015)
The background of this research is low activity and students learning outcomes on subjects Kesehatan, Keselamatan Kerja (K3) and Higiene Sanitasi at SMK Negeri 3 Solok. Purpose of this research to increase activity and students learning outcomes using power point. Type of research is Classroom Action Research, with three cycles. This research consisted of four stage planning, acting, observation, and reflection. Data used primary data were obtained directly from students activities form and students learning outcomes on subjects K3 and Higiene Sanitasi. Data obtainedare tabulated and calculated the percentage of achievement of learning objective. The result showed media poer point can increase activity and students learning outcomes on subjects K3 and Higiene Sanitasi. This matter can be seen increased activity and learning outcomes master learning target above the value 71.Word keys : activites, learning outcomes, students, media, and power point